The Effect of Financial Ratios and Sustainability Report Disclosure on Company Value - Nunuk Andriastuti (Pusat Publikasi Nusantara, 2025)
This study aims to analyze the effect of Company Characteristics measured using the Profitability Ratio, Leverage, Liquidity, and Company Size on Company Value with Sustainability Reports as intervening variables. The data used in this study are secondary data sourced from the Annual Report and Sustainability Report of state-owned companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The research sample was selected using the purposive sampling method so that 20 companies were obtained as samples. Data analysis used for hypothesis testing is panel data analysis using the Eviews 12 program. The findings show that profitability proxied by Return on Asset and Earning per Share is not proven to have a positive effect on firm value, Leverage proxied by Debt to Equity Ratio is not proven to have a positive effect on firm value, while leverage proxied by Long-term Debt to Equity Ratio is proven to have a positive effect on firm value, liquidity proxied by Current Ratio and Cash Ratio is not proven to have a positive effect on firm value, sustainability reports are proven to have a positive effect on firm value, and firm size proxied by total assets and total employees is not proven to have a positive effect on firm value.